ALDH2 attenuates myocardial pyroptosis through breaking down Mitochondrion-NLRP3 inflammasome pathway in septic shock - Ying Zhang; Ying Zhang; Ying Zhang; Ying Zhang; Ying Lv; Ying Lv; Ying Lv; Ying Lv; Qingju Zhang; Qingju Zhang; Qingju Zhang; Qingju Zhang; et al. (Frontiers Media S.A., 2023)
Cell survival or death is critical for cardiac function. Myocardial pyroptosis, as a newly recognized programmed cell death, remains poorly understood in sepsis. In this study, we evaluated the effect of aldehyde dehydrogenase (ALDH2) on myocardial pyroptosis and revealed the underlying mechanisms in sepsis. We established a septic shock mice model by intraperitoneal injection of Lipopolysaccharide (LPS, 15 mg/kg) 12 h before sacrifice. It was found that aldehyde dehydrogenase significantly inhibited NOD-like receptor protein 3 (NLRP3) inflammasome activation and Caspase-1/GSDMD-dependent pyroptosis, which remarkably improved survival rate and septic shock-induced cardiac dysfunction, relative to the control group. While aldehyde dehydrogenase knockout or knockdown significantly aggravated these phenomena. Intriguingly, we found that aldehyde dehydrogenase inhibited LPS-induced deacetylation of Hydroxyacyl-CoA dehydrogenase trifunctional multienzyme complex α subunit (HADHA) by suppressing the translocation of Histone deacetylase 3 (HDAC3) from nuclei to mitochondria. Acetylated HADHA is essential for mitochondrial fatty acid β-oxidation, and its interruption can result in accumulation of toxic lipids, induce mROS and cause mtDNA and ox-mtDNA release. Our results confirmed the role of Histone deacetylase 3 and HADHA in NOD-like receptor protein 3 inflammasome activation. Hdac3 knockdown remarkedly suppressed NOD-like receptor protein 3 inflammasome and pyroptosis, but Hadha knockdown eliminated the effect. aldehyde dehydrogenase inhibited the translocation of Histone deacetylase 3, protected ac-HADHA from deacetylation, and significantly reduced the accumulation of toxic aldehyde, and inhibited mROS and ox-mtDNA, thereby avoided NOD-like receptor protein 3 inflammasome activation and pyroptosis. This study provided a novel mechanism of myocardial pyroptosis through mitochondrial Histone deacetylase 3/HADHA- NOD-like receptor protein 3 inflammasome pathway and demonstrated a significant role of aldehyde dehydrogenase as a therapeutic target for myocardial pyroptosis in sepsis.